A study on fuzzy-AHP analysis for carbon neutrality in container terminals in Korea - Hyun-Woo Kim; Yong Seok Choi; Jae Eun Lee (Asian Journal of Shipping and Logistics (AJSL), 2025)
The purpose of this study was to investigate the relative importance of determinants that should be considered first in order for container terminals to realize carbon neutrality and become an eco-friendly port. Three upper determinants and 12 lower determinants were derived through the two-stage Delphi survey to derive questionnaire items. The factors determined by the container terminal operation experts were surveyed, and priorities were identified using the Fuzzy-Analytic Hierarchy Process(Fuzzy-AHP) technique. As a result, the importance of the top three priority factors was evaluated in the order of improvement of laws and systems, energy efficiency, and low-carbon infrastructure construction, confirming that to realize carbon neutrality at container terminals, it was necessary to first consider improving laws and systems that reflected realistic problems. According to the results of the priority analysis, the introduction of energy-saving equipment, the introduction of the AMP mandatory system, the provision of incentives to realize carbon neutrality, the establishment and implementation of low-carbon port policies, and the implementation of carbon-bearing regulatory measures, which are sub-factors of legal and institutional improvement, which were the highest importance of the top factors, ranked 2nd to 5th.
Keywords: 650; Carbon Neutral; Container Terminal; Delphi Survey; Factor Analysis; Fuzzy-AHP